Supervision System in The Effectiveness of Zakat Utilization in Baznas of Bengkulu Province - Hariya Toni; Dede Mercy Rolando; Yasril Yazid; Rafdeadi Rafdeadi (AJIS: Academic Journal of Islamic Studies, 2022)
This study aims to examine the supervisory system of BAZNAS of Bengkulu Province in the empowerment of zakat with the aim to alleviate poverty. The research method used in this research is a qualitative approach with a phenomenological paradigm to build the reality of ideas. The data collection methods used were observation, interviews, and documentation which were then analyzed by using the Miles & Huberman interactive model, namely data reduction, data presentation, and conclusion drawing or verification. The results obtained show that the National Amil Zakat Agency (BAZNAS) of Bengkulu Province community empowerment was carried out in the form of direct and indirect supervision by BAZNAS of Bengkulu Province. The form of direct supervision was a form of preventive supervision (Concurrent Control) and initial supervision (Feed Forward Control), while the form of indirect supervision was feedback control in which this supervision was used to measure the results of an activity that had been carried out. The two forms of supervision were the types of internal control carried out by directly related parties and the type of preventive and repressive supervision to avoid deviations in the implementation of zakat empowerment activities. However, the supervision of BAZNAS of Bengkulu Province community empowerment needs to apply more detailed and clear indicators of empowerment success for each community empowerment program. In addition, BAZNAS needs to make a Standard Operating Procedure (SOP) for the implementation of the empowerment program by not only showing it but also implementing coaching and mentoring to a clear stage of achieving independence